The Paycheck Protection Program Liquidity Facility - Desi Volker (Federal Reserve Bank of New York, 2021)
To bolster the effectiveness of the Small Business Administration's Paycheck Protection Program (PPP), the Federal Reserve, with the backing of the Secretary of the Treasury, established the Paycheck Protection Program Liquidity Facility (PPPLF). The facility was intended to supply liquidity to financial institutions participating in the PPP and thereby provide relief to small businesses and help them maintain payroll. In this article, we lay out the background and rationale for the creation of the facility, cover the salient features of the PPP and the PPPLF, and analyze the facility's loan take-up. Our findings suggest that the PPPLF played an important role in expanding the supply of credit to smaller banks and nondepository institutions and that these institutions were more likely to originate PPP loans to businesses on the smaller end of the scale.
Keywords: G0; G2; G21; G23; G28; 330; PPP; PPPLF; SBA; CARES Act; Federal Reserve lending facilities